Combined hepatocellular-cholangiocarcinoma: An analysis of clinicopathological characteristics after surgery. Issue 38 (September 2019) - Zhang, Hao; Yu, Xiaojiong; Xu, Jian; Li, Juan; Zhou, Yao
Abstract : Abstract: Combined hepatocellular-cholangiocarcinoma (CHCC) is a rare type of primary liver cancer (PLC). The aim of this study was to investigate the disease characteristics in CHCC patients and compare them with those in hepatocellular carcinoma (HCC) or intrahepatic cholangiocarcinoma (ICC). The perioperative and follow-up data of CHCC patients (n = 15), HCC patients (n = 577), and ICC patients (n = 61) were retrospectively analyzed, and the clinicopathological characteristics were compared among these 3 groups. In the CHCC group, the serum level of AFP was significantly higher than that of the ICC group ( P  = .002), and the CA19-9 level was higher than that of the HCC group ( P  = .011). The positive rates of CK7 and CK19 expression were higher in CHCC group than in HCC group (both P  < .001), while the positive rates of Glypican–3 and Hepatocyte expression were higher in CHCC group than in ICC group (both P  < .001). Meanwhile, the CHCC patients were likely to have undergone more MJH/LT than the HCC patients ( P  = .037) and the ICC patients ( P  = .011). Macrovascular invasion and lymph node metastasis in the CHCC group were significantly higher but satellite lesions were similar, compared to the HCC group. Both the 1-year disease-free survival (DFS) and the 1-year overall survival (OS) for the CHCC patients were worse than those for the HCC patients. AFP ≥ 400 ng/ml, tumor size ≥5 cm, tumor number ≥2, macro- and microvascular invasion, distant metastasis and positive margin were risk factors for both DFS and OS for the PLC patients. Multivariate analysis also confirmed that ICC and lymph node metastasis were risk factors for DFS and MJH/LT was risk factor for OS. CHCC patients appear to have intermediate clinical characteristics in comparison with the HCC and ICC patients, and the 1-year DFS and OS for the CHCC patients was worse than the HCC patients, but similar to the ICC patients.